The need of creative thinking in Indian medical education - Yelavarthi, Raghu (International Journal Of Community Medicine And Public Health, 2022)
Background: Creative thinking provides an innovative and imaginative way to solve complicated problems. It has the potential to be widely used in medical education, especially early in a first-year medical student’s career as part of their foundation course. Creative thinking participants develop crucial life-long learning skills to cope with varied ideas and collaborative teamwork. Methods: A survey of first-year students who took the course revealed that they need more creative ways of teaching. They require their minds to be ignited by their thoughts and teamwork rather than general theories taught monotonously. For this, creative thinking modules should be taught to the students necessarily. Two modules on creative thinking that should be implemented have been briefly described. Results: This paper stresses the importance of introducing creative thinking modules in the foundation medical course to reinforce the principles taught for practical understanding and implementation by the student in their career. Projects that failed throughout history in science and technology did so not because of flaws in technique or methodology, but because people were locked in their preconceptions, set attitudes, and old habits. To thrive and prosper, science, technology, engineering, and math (STEM) industries require innovation. Conclusions: It is of a strong opinion that in the Indian context, creative thinking modules should be implemented in the foundation course for first-year medical students. This will positively impact attitudes, ethics, and communication skills, which will be the foundation of their entire medical education and career.